2018
DOI: 10.3390/ijerph15081616
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Risk-Based Intervention on Piped Water Quality in Rural Communities: The Case of Mid-Western Nepal

Abstract: Ensuring universal access to safe drinking water is a global challenge, especially in rural areas. This research aimed to assess the effectiveness of a risk-based strategy to improve drinking water safety for five gravity-fed piped schemes in rural communities of the Mid-Western Region of Nepal. The strategy was based on establishing community-led monitoring of the microbial water quality and the sanitary status of the schemes. The interventions examined included field-robust laboratories, centralized data man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…This study also highlighted the fact that sanitary inspection results at the household level did not reliably predict microbial quality of stored water, as has been raised by other studies [21,34]. Instead, only one variable is significantly correlated with storage water quality (last paragraph in Section 3.2).…”
Section: Factors Related To Water Qualitysupporting
confidence: 52%
See 2 more Smart Citations
“…This study also highlighted the fact that sanitary inspection results at the household level did not reliably predict microbial quality of stored water, as has been raised by other studies [21,34]. Instead, only one variable is significantly correlated with storage water quality (last paragraph in Section 3.2).…”
Section: Factors Related To Water Qualitysupporting
confidence: 52%
“…These findings raise questions about the adequacy and completeness of common sanitary inspection checklists at the household for predicting actual health risks. These finding are corroborated by Robinson et al [21], who argued that sanitary inspection forms in rural Nepal, while useful for general risk assessment and risk management of spring-fed piped water schemes, cannot replace regular water quality testing for monitoring purposes.…”
Section: Factors Related To Water Qualitymentioning
confidence: 65%
See 1 more Smart Citation
“…Snoad et al 13 utilized logistic regression to predict the fecal contamination by SI and their AUC values were low (range 0.41–0.64). Other authors also used multiple statistical analyses and found that SI variables could not explain well the water quality 10 , 14 , 16 , which imply that our models (with AUC values of 0.69 and 0.84) were slightly better in predicting the water quality at POU, using SI data.…”
Section: Discussionmentioning
confidence: 71%
“…The pipe-water supply according to the study was characterized by an irregular flow that runs weekly or twice a week and in some cases, thrice a month [5]. The irregular or intermittent piped water supply was reported to serve as a causative medium through which contaminates entered the water channels, thus increasing the risk to public health [7,19,20].…”
Section: Introductionmentioning
confidence: 99%